Values paradigm of education for sustainable development - I A Shmeleva (Peoples' Friendship University of Russia (RUDN University), 2009)
The problems of the psychological and philosophical maintenance of education for Sustainable Development in the context of the purposes of Strategy for ESD adopted by the United Nations European Commission for Europe are discussed. Changes in the values priorities are considered to be the core issues of the psychological and philosophical maintenance of education for sustainable development.